Group B Streptococcal Endocarditis in Obstetric and Gynecologic Practice - Antonio Crespo; Avi S. Retter; Bennett Lorber (Hindawi Limited, 2003)
Background: We describe a case and review ten other instances of group B streptococcal endocarditis in the setting of obstetric and gynecologic practice reported since the last review in 1985.